Peningkatan Pemahaman Kompetensi Hard Skill dan Soft Skill Siswa SMK Al Ansori Sebagai Persiapan Menuju Dunia Kerja - Soedjatmoko; Sarmin; Sri Winda Hardiyanti Damanik; Aditya Suryaman; Pegi Pitria Putri; Ririn Uke Saraswati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This community service activity carried out by lecturers and students aims to improve the understanding of hard skills and soft skills of SMK Al Ansori students in preparation for the world of work. In the era of globalization and rapid technological development, a balanced competency between technical skills (hard skills) and interpersonal skills (soft skills) is very important. This activity consists of a series of workshops, trainings, and simulations designed to provide students with hands-on experience in skills development relevant to industry demands. Through an interactive approach, students will be trained in various aspects, such as effective communication, teamwork, time management, as well as technical skills according to their majors. In addition, this activity also involves discussions with professionals in the field to provide insight into the world of work and the challenges faced. The expected outcome of this activity is an increase in students' confidence, a better understanding of the importance of the combination of hard and soft skills, and their readiness to enter the competitive world of work. Thus, this activity is expected to contribute to improving the quality of SMK Al Ansori graduates in facing future career challenges.